2011
DOI: 10.1186/1756-0500-4-255
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported poor oral hygiene among in-school adolescents in Zambia

Abstract: BackgroundDental health is a neglected aspect of adolescent health globally but more so in low-income countries. Secondary analysis using the 2004 Zambia Global School-Based Health Survey (GSHS) was conducted in which we estimated frequencies of relevant socio-demographic variables and explored associations between selected explanatory variables and self-reported poor oral hygiene (not cleaning or brushing teeth) within the last 30 days of the completion of questionnaire.FindingsMost of the 2257 respondents we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
3
16
0
Order By: Relevance
“…As found in previous studies [ 9 , 11 , 12 ], this study also found that males were at greater risk of sub-optimal tooth brushing than females. Contrary to a number of other studies [ 8 , 10 , 11 , 13 , 14 , 15 , 16 ], lower socioeconomic status (assessed here with hunger) was not found to be associated with sub-optimal tooth brushing.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As found in previous studies [ 9 , 11 , 12 ], this study also found that males were at greater risk of sub-optimal tooth brushing than females. Contrary to a number of other studies [ 8 , 10 , 11 , 13 , 14 , 15 , 16 ], lower socioeconomic status (assessed here with hunger) was not found to be associated with sub-optimal tooth brushing.…”
Section: Discussionsupporting
confidence: 89%
“…The recommended tooth brushing (at least twice daily) prevalence among school children in studies in other regions found in nine African countries 77.3% [ 9 ] and in the Pacific in Vanuatu 62%, in Tonga 70% and Pohnpei 78% [ 10 ]. Sociodemographic factors (younger age [ 8 ], being male [ 9 , 11 , 12 ], low socioeconomic status [ 8 , 10 , 11 , 13 , 14 , 15 , 16 ], rural residence [ 7 ], health risk behaviours including smoking [ 16 , 17 ], alcohol and cannabis use [ 12 ], inadequate exercise [ 16 ], infrequent fruits and/or vegetables consumption [ 9 , 18 ], lack of protective factors [ 9 , 19 , 20 ], and psychological distress [ 9 ] have been identified as risk factors for poor oral hygiene among adolescents. In a study in India a significant association between overweight and obese children and caries prevalence was found [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown that the use of substances, such as cigarettes, alcohol, and cannabis, was associated with less favourable tooth‐brushing habits [24, 53]. Health risk behaviours tend to occur in the same social context.…”
Section: Discussionmentioning
confidence: 99%
“…Tooth‐brushing habits are enmeshed in complex daily habits and can indicate the wider context of adolescents’ lifestyles [8, 10, 19]. The association between tooth‐brushing frequency and elements of lifestyle, such as dietary behaviour, physical activity, sedentary behaviour, nutritional status, smoking, and alcohol and cannabis use, have been demonstrated [4, 15, 20–24]. It has been suggested that lifestyle might reflect the health consciousness and personal characteristics of a person and is also associated with psychosocial factors shaped by the local cultures and shared contexts [11, 25–28].…”
Section: Introductionmentioning
confidence: 99%
“…Poor oral hygiene have commonly been reported among both children and adolescents and may lead to a number of oral health problems such as dental caries, gingivitis, periodontitis and tooth loss [ 24 , 25 ]. For example in Zambia, the prevalence of poor oral hygiene in 10–14 year old adolescents (2011) was 10% and in Nigeria the corresponding figures among 11–14 years olds was found to be 32% (2011) [ 26 , 27 ]. Among adolescents in Tanzania, the prevalence of poor oral hygiene was found to be as high as 65–99% (1988, 1996) and the occurrence of gingivitis as high as 80–90% [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%